Understanding Islamic Banking Usage Continuance in Indonesia: A Relevance of Religiosity Perspective - Lestari, Dini Maualana; Furwanti, Reni; Masri, Syahril (Invest Journal of Sharia & Economic Law, 2025)
This study explores and analyzes religiosity as a key factor in muamalah activities to boost Islamic banking customers' intention to continue using the service. This focus arises from the intense competition in Indonesia's Islamic financial industry. Despite this competition, the Islamic banking sector still has a relatively small percentage of loyal customers, contributing to its low market share in the country. Therefore, banks must devise strategies that leverage religious factors to enhance customers' continuance intention usage (CUI). This quantitative study employed a survey method, utilizing structural equation modeling (SEM-AMOS) to meet its research objectives. The study selected Islamic banking customers as its sample and gathered 403 participants through convenience sampling. The findings indicate that this study adjusted the religiosity indicator to assess economic activity, particularly customer behavior. Additionally, the model demonstrated that religiosity can significantly enhance Islamic banking customers' CUI. This study offers policy recommendations for regulators in the Islamic banking industry, emphasizing the importance of religious factors in attracting customer continuance intention usage, as most Indonesian Muslims exhibit greater confidence in such factors.